2005
DOI: 10.1111/j.0022-202x.2005.23688.x
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the CYLD gene in Brooke–Spiegler Syndrome, Familial Cylindromatosis, and Multiple Familial Trichoepithelioma: Lack of Genotype–Phenotype Correlation

Abstract: Brooke-Spiegler syndrome (BSS), familial cylindromatosis (FC), and multiple familial trichoepithelioma (MFT), originally described as distinct entities, share overlapping clinical findings. Patients with BSS are predisposed to multiple skin appendage tumors such as cylindroma, trichoepithelioma, and spiradenoma. FC, however, is characterized by cylindromas and MFT by trichoepitheliomas as the only tumor type. These disorders have recently been associated with mutations in the CYLD gene. In this report, we desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
128
1
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(135 citation statements)
references
References 13 publications
4
128
1
2
Order By: Relevance
“…We performed haplotype analysis for these two geographically distant pedigrees and found that the mutations resulted from two independent mutational events, suggesting that is the mutations represent a mutational hotspot on the CYLD gene [Grossmann et al, 2013]. Our results correlate well with the data reported in the literature supporting the assumption that this is a mutational hotspot on the gene: the c.2806C>T, p.Arg936X nonsense mutation has been described in all three allelic variants in the disease spectrum caused by CYLD mutations 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 7 and results in different symptom severity as well as the development of different clinical variants [Bignell et al, 2000;Bowen et al, 2005;Grossmann et al, 2013;Saggar et al, 2008;Kazakov et al, 2009;Nagy et al, 2013]. [Bignell et al, 2000;Grossmann et al, 2013;Saggar et al, 2008;Nasti et al, 2009;Ying et al, 2012 …”
Section: Summary Of Hungarian Bss Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…We performed haplotype analysis for these two geographically distant pedigrees and found that the mutations resulted from two independent mutational events, suggesting that is the mutations represent a mutational hotspot on the CYLD gene [Grossmann et al, 2013]. Our results correlate well with the data reported in the literature supporting the assumption that this is a mutational hotspot on the gene: the c.2806C>T, p.Arg936X nonsense mutation has been described in all three allelic variants in the disease spectrum caused by CYLD mutations 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 7 and results in different symptom severity as well as the development of different clinical variants [Bignell et al, 2000;Bowen et al, 2005;Grossmann et al, 2013;Saggar et al, 2008;Kazakov et al, 2009;Nagy et al, 2013]. [Bignell et al, 2000;Grossmann et al, 2013;Saggar et al, 2008;Nasti et al, 2009;Ying et al, 2012 …”
Section: Summary Of Hungarian Bss Patientsmentioning
confidence: 99%
“…BSS, FC and MFT1 were originally described as distinct clinical entities, but due to their overlapping clinical symptoms and their manifestation within the same families, they are now considered as a clinical variants that represent a phenotypic spectrum of a single entity Welch et al, 1968;Young et al, 2006;Oranje et al, 2008]. [Bignell et al, 2000;Bowen et al, 2005;Grossmann et al, 2013;Linos et al, 2011;Lv et al, 2008;Kacerovska et al, 2013;Saggar et al, 2008;Van den Ouweland et al, 2011;Oiso et al, 2004;Zhang et al, 2006;Kazakov et al, 2009;Kazakov et al, 2011;Nagy et al, 2013]. Therefore, it has been hypothesized that BSS, FC and MFT1 are not different disease entities, but represent a phenotypic spectrum of the same disease.…”
mentioning
confidence: 99%
“…Most CYLD mutations identified in cylindromatosis are frameshift or nonsense mutations that remove all or part of the catalytic domain of CYLD (Bignell et al, 2000;Poblete-Gutie´rrez et al, 2002;Hu et al, 2003;Scheinfeld et al, 2003;Tobin et al, 2003;Bowen et al, 2005;Heinritz et al, 2006) (Figure 2). In addition, a few missense mutations have been identified, but how they affect CYLD function is unclear .…”
Section: Ikba-related Immune Deficiencymentioning
confidence: 99%
“…1,2 Although typically observed sporadically as solitary neoplasms, they may rarely be multiple in the setting of the Brooke-Spiegler syndrome. 3,4 Similar to adenoid cystic carcinoma of the breast and salivary glands, the MYB-NFIB gene fusion product, due to a t(6;9)(q22 ∼ 23; p23 ∼ 24) translocation, has recently been demonstrated in a subset of dermal cylindromas, resulting in overexpression of the MYB protein. [5][6][7][8][9] MYB is a leucine zipper transcription factor and has an important role in cell proliferation, apoptosis and cell differentiation.…”
mentioning
confidence: 99%